2019
DOI: 10.1103/physrevmaterials.3.014412
|View full text |Cite
|
Sign up to set email alerts
|

Trimer-based spin liquid candidate Ba4NbIr3O12

Abstract: Ba4NbIr3O12, a previously unreported material with a triangular planar geometry of Ir3O12 trimers, is described. Magnetic susceptibility measurements show no magnetic ordering down to 1.8 K despite the Curie-Weiss temperature of -13 K. The material has a very low effective magnetic moment of 0.80 μB/f.u. To look at the lower temperature behavior, the specific heat (Cp) was measured down to 0.35 K; it shows no indication of magnetic ordering and fitting a power law to Cp vs. T below 2 K yields the power α = ¾. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
8
26
0
Order By: Relevance
“…First, previous studies [25] have shown that no magnetic ordering occurs in Ba 5 CuIr 3 O 12 down to 4 K despite a Curie temperature of −98 K, which suggests a possible QSL ground state. Moreover, a related compound Ba 4 NbIr 3 O 12 has recently been proposed to be a QSL candidate material [27]. Second, the nature of the Ir magnetic moments in this system is quite peculiar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous studies [25] have shown that no magnetic ordering occurs in Ba 5 CuIr 3 O 12 down to 4 K despite a Curie temperature of −98 K, which suggests a possible QSL ground state. Moreover, a related compound Ba 4 NbIr 3 O 12 has recently been proposed to be a QSL candidate material [27]. Second, the nature of the Ir magnetic moments in this system is quite peculiar.…”
mentioning
confidence: 99%
“…The 5d Ir ions have a strong spin-orbit coupling and form face-sharing Ir 4+ trimers, which renders the usual local J eff =1/2 moment picture [28,29] inapplicable due to enhanced covalency. Instead, molecular orbitals at each Ir trimer are expected to form [24,27,30]. Finally, the material contains intrinsic disorder due to site mixing between Cu and Ir, as well as Cu displacement from the prism center [25,26] [see Fig.…”
mentioning
confidence: 99%
“…Recently, unconventional electronic and magnetic ground states have been reported in compounds with the basic units of Ir-trimers, i.e. three face-sharing IrO 6 octahedra, which are much less explored so far [15][16][17]. For instance, both charge density wave and canted antiferromagnetic order have been observed in the quasione-dimensional compound BaIrO 3 [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Sr 2 CaReO 6 , and Ba 4 NbIr 3 O 12 -illustrating such a scenario have been reported, so far. [6][7][8][9][10][11] In this work, we report the synthesis, structure, and magnetic properties of an ordered double perovskite Sr 2 NaOsO 6 . Though this compound was first synthesized by Sleight et al in 1962, its structure and magnetic properties were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Discovering materials with magnetic frustrated states such as spin liquid and spin glass in perovskites are of particular interest to the solid matter chemistry and physics communities, however, unfortunately only very few examples – Sr 2 FeMO 6 (Nb, Mo, Te), Sr 2 CaReO 6 , and Ba 4 NbIr 3 O 12 ‐ illustrating such a scenario have been reported, so far. [ 6–11 ]…”
Section: Introductionmentioning
confidence: 99%